Medication Behavior of Patients with Chronic Obstructive Pulmonary Disease at Home, Thasala District, Nakhon Si Thammarat Province - ทองประสิทธิ์, สุธิศา; หนูนิล, นัยนา; สรรพวีรวงศ์, จิราภรณ์ (Princess of Naradhiwas University Journal, 2018)
Use the right medications are vital and necessary for saving the lives of patients with chronic obstructive pulmonary disease (COPD) and for clearing their airways and breathing effectively. However, very little research has been conducted about how these medications are behavior at home both orally and through devices called inhalers. Thus, this descriptive research study aimed to explore the medication behavior of patients with COPD at home in Thasala district, Nakhon Si Thammarat Province. The sample was composed of two hundred and seventy-four stable COPD patients whose selected using quota sampling method from 10 subdistrict. The data were collected in the period from September through December 2016. The research instruments employed were general information and health questionnaires, drug management questionaires. The questionnaires had CVI=0.85 and Cronbach’s alpha coefficient=0.80. Descriptive statistics was used to data analysis. The results showed that most of the participants had appropriate oral medical behavior procedures; however, the lowest scores were for checking expiration date of the medications ( =2.18, S.D.=.92) and taking medications on time ( =2.39, S.D.=0.81). For the inhaler medications behavior, the lowest behavior scores included checking the medication device before use to see if it was empty ( =1.98, S.D.=.83) and cleaning the inhaler’s mouthpiece ( =2.76, S.D.=.86). This study suggests that nurses who care for patients with COPD should assess the patients’ capability and problems in oral and inhaler medications behavior. Also, promoting knowledge and understanding of medication behavior will enhance the effectiveness of patients’ treatment.